DETERMINAN PERGERAKAN IHSG PADA PERIODE 2000-2009 - , Rahaditomo Muktiwibowo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The movement of stock prices traded in the Indonesia Stock Exchange can be monitored from the fluctuation of the Jakarta Composite Index (JCI or IHSG) enabling one to establish whether the market is bullish or otherwise bearish. Inconsistencies from previous researches on the effects of economy indicators toward stock indices has created research gaps. Thru this research some economy indicators with inconsistencies in previous research such as BI rate, oil price, gold price, exchange rate IDR/USD, Nikkei 225 index and Dow Jones Industrial Average (DJIA) will be further analyzed. This research will analyze the effects of the aforementioned indicators and establish the determinant towards the movement of the JCI. Sample of this research will be available monthly information regarding BI rate, oil price, gold price, exchange rate IDR/USD, Nikkei 225 index and DJIA within the period of 2000 up to 2009. Such indicators will be analyzed using Linear Multiple Regression, satisfying classical assumption tests beforehand. The result of this research has indicated the BI rate is the determinant of JCI movement. BI rate has a significant negative effect towards the JCI. While other indicators have significant impact both simultaneously or partially. The unique condition of the Indonesia stock market within the observed period notably the dominance of the mining sector has opposite outcome of previous research on the effects oil prices towards stock indices. The increase of gold prices also does not reflect the predicted effects toward the JCI.